Phytochemical composition and antioxidant activity of Tuscan bee pollen of different botanic origins - V. Domenici; M. Gabriele; E. Parri; A. Felicioli; S. Sagona; L. Pozzo; C. Biondi; L. Pucci (Chiriotti Editori, 2015)
Within the apicultural products, the honey bee-pollen is growing in commercial interest due to its high nutritional properties. For the first time, bee-pollen samples from Tuscany (Italy) were studied to evaluate botanical origin, phytochemical composition and antioxidant activity. The investigated pollen loads were composed of three botanical families: Castanea, Rubus and Cistus. The highest levels of proteins and lipids were detected in Rubus pollen. Castanea pollen contained greater polyphenols, flavonoids and anthocyanins content, while the highest flavonols level was detected in Cistus pollen. These results were also confirmed by front-face fluorescence spectroscopy, used here, for the first time, as a fast tool to characterize bee-pollens.